The Influence of YouTube Content Creativity on the Income of Local YouTubers in Tapen District, Bondowoso Regency - Ivo Adi Widodo; Dyan Yuliana; Siti Seituni (Universitas Islam Raden Rahmat, Malang, 2026)
This study discusses the influence of YouTube content creativity on the income of local YouTubers in Tapen District, Bondowoso Regency. YouTube's rapid development in the digital era has made competition between content creators even higher, so creativity is an important factor to attract viewers and increase revenue. This study used a quantitative approach involving 50 active local YouTubers who have been earning from YouTube for more than one year. Data were collected through questionnaires and analyzed using a partial t-test. The results of the study show that content creativity has a positive and significant effect on the income of local YouTubers in Tapen District. Creative elements such as unique video ideas, visual and audio quality, title and thumbnail strategies, and upload consistency have proven to help increase your audience and AdSense revenue. These results show that the higher the content creativity, the greater the income opportunities for local YouTubers in the digital creative economy.